Mandibular Clinical Arch Forms in Iraqi Population: A National Survey - Ali, Munther A.; Yassir, Yassir A. (Diagnostics (Basel), 2022)
Background: This study aims to identify mandibular clinical arch forms and dimensions in the Iraqi population. Materials and methods: The study sample consisted of pre-treatment mandibular study models of the Iraqi population. The most labial aspect of 13 proximal contact areas was digitized using AutoCAD software to determine the clinical bracket point for every tooth. The dental arches were classified into three types: tapered, ovoid, and square. The arch dimensions were identified using four linear and two proportional measurements. Results: A total of 1005 study models were collected. The arch forms were distributed as ovoid (47%), tapered (36.2%), and square (16.8%), with no significant difference in the distribution between Arabs and Kurds. The ovoid arch form was predominant in class I and class III malocclusion, while the tapered arch form was predominant in class II. All the linear measurements were greater in the males than in the females. The arch widths decreased as the arch form shifted from square to ovoid to tapered, while the arch depths showed the reverse relation. Conclusions: According to this study, ovoid and tapered archwires should suit the majority of Iraqi patients. The ovoid arch form was the most predominant in the subjects with class I and class III malocclusion, while the tapered arch form was the most predominant in the class II subjects.